Earnings Management in Polish Companies - Brzeszczyński, Janusz; Gajda, Jerzy; Schabek, Tomasz (Comparative Economic Research. Central and Eastern Europe, 2012)
This paper presents results of the investigation of a phenomenon known as "earnings management'' (EM) among the companies listed on the Polish stock market. The distribution of earnings per share (EPS) for the stocks around the threshold value of "zero" and the threshold of "recent performance" was analyzed in the period of years 1997-2010. Moreover, the changes of earnings for the stocks, which are suspected to manipulate their earnings, were also investigated. The results, which indicate asymmetric distribution of earnings around the zero threshold along with the relative deterioration of earnings in the year following the period when the companies were suspected to conduct earnings management practices, provide evidence that this phenomenon exists among Polish stock market companies.